{N′-[(E)-(5-Bromo-2-oxidophenyl)(phenyl)methylene]-4-chlorobenzohydrazidato}pyridinenickel(II) - Zheng, Chang-Zheng (International Union of Crystallography, 2009)
The asymmetric unit of title complex, [Ni(C(20)H(12)BrClN(2)O(2))(C(5)H(5)N)], contains one complex with the central Ni atom in a slightly distorted square–planar environment, formed by the tridentate hydrazone and the monodentate pyridine ligands, with N atoms in a trans arrangement about the Ni atom.